2015
DOI: 10.1037/a0039466
|View full text |Cite|
|
Sign up to set email alerts
|

When and why do old adults outsource control to the environment?

Abstract: Old adults' tendency to rely on information present in the environment rather than internal representations has been frequently noted, but is not well understood. The fade-out paradigm provides a useful model situation to study this internal-to-external shift across the life span: Subjects need to transition from an initial, cued task-switching phase to a fade-out phase where only one task remains relevant. Old adults exhibit large response-time "fade-out costs", mainly because they continue to consult the tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
1
12
1
Order By: Relevance
“…The current findings also support literature showing that older adults attend to and outsource control to the environment, possibly because doing so may reduce demands on self-initiated processing (Lindenberger & Mayr, 2014). However, in contrast to some studies showing that older adults have even stronger attention to and reliance on the environment than younger adults (Mayr et al, 2015; Spieler et al, 2006), we found equivalent experience-driven acquisition and shifting of control for younger and older adults. This may reflect that younger adults may be disinclined to attend to environmental information when doing so requires extra effort and may harm performance (as with inspecting task cues that are no longer needed for task performance; Mayr et al, 2015; Spieler et al, 2006) but they may attend to environmental information when it does not require effort (i.e., because it occurs implicitly) and may benefit performance (as in the case of PC in the present study).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The current findings also support literature showing that older adults attend to and outsource control to the environment, possibly because doing so may reduce demands on self-initiated processing (Lindenberger & Mayr, 2014). However, in contrast to some studies showing that older adults have even stronger attention to and reliance on the environment than younger adults (Mayr et al, 2015; Spieler et al, 2006), we found equivalent experience-driven acquisition and shifting of control for younger and older adults. This may reflect that younger adults may be disinclined to attend to environmental information when doing so requires extra effort and may harm performance (as with inspecting task cues that are no longer needed for task performance; Mayr et al, 2015; Spieler et al, 2006) but they may attend to environmental information when it does not require effort (i.e., because it occurs implicitly) and may benefit performance (as in the case of PC in the present study).…”
Section: Discussioncontrasting
confidence: 99%
“…If attention does not at least partially bleed over into the processing of the irrelevant word, then learning/updating of PC cannot occur and control settings will not shift from the early to late segment. Finding that older adults are able to shift control similarly to younger adults with experience as the guide may suggest that the concept of habitual attention extends to attention control and shifting in a conflict task, and additionally support prior observations demonstrating older adults’ tendency to offload cognitive control to the environment (e.g., Mayr et al, 2015; Spieler et al, 2006).…”
Section: Methodssupporting
confidence: 77%
“…However, the sorts of environmental statistics experienced in the real world vary considerably over the lifespan, as do the cognitive capacities that might be necessary to respond to them, raising the question of how these adaptive learning processes may change. Across different task domains, performance limitations in children and older adults are often either due to preservation or an increased impact of environmental information on behavior (Alarcón and Bonardi, 2020;Carroll et al, 2007;Cepeda and Munakata, 2007;Chatham et al, 2009;Craik and Bialystok, 2006;Crone et al, 2004a,b;De Boer et al, 2017;Gonthier et al, 2019;Head et al, 2009;Lindenberger and Mayr, 2014;Mayr et al, 2015;Munakata et al, 2012;Ridderinkhof et al, 2002;Rutledge et al, 2009;Troller-Renfree et al, 2020). Previous work has identified lifespan differences in learning (Eppinger et al, 2008(Eppinger et al, , 2009(Eppinger et al, , 2013Chowdhury et al, 2013;Crone and Van der Molen, 2004;Hämmerer et al, 2011;Rutledge et al, 2009;Samanez-Larkin et al, 2010, 2014Van den Bos et al, 2012;Van Der Schaaf et al, 2011) and suggested that they might relate to normative impairments in belief updating (De Boer et al, 2017;Hämmerer et al, 2019;.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Halen-Hayes marker set method ( Figure 6) [17], the walking characteristics of all testers were measured by attaching a total of 29 markers. As the walking characteristics of the elderly could change [18,19] due to their higher sensitivity [20,21] to environmental changes than the non-elderly, the measurements were done after conducting 3-5 rounds of practice walking back and forth ( Figure 7) in a manner that allowed adaptation to the clothes worn, the marker set and the measuring environment in order to minimize the errors attributable to such factors. For normal walking, the activity was carried out on a 6 m long walkway, and at this time, a comfortable environment was ensured to the best possible extent so that the usual walking characteristics could be obtained.…”
Section: Measurements and Results Of The Characteristics Of Normal Wamentioning
confidence: 99%